Evidence for global teleconnections in a late Pleistocene speleothem record of water balance and vegetation change at Sudwala Cave, South Africa. (15th February 2015) - Green, Helen; Pickering, Robyn; Drysdale, Russell; Johnson, Brett C.; Hellstrom, John; Wallace, Malcolm
Abstract: Understanding the global response to millennial-scale climatic events is essential to our comprehension of climatic teleconnections and projection of future change, however the extent and nature of their expression in areas of the Southern Hemisphere is often viewed as equivocal. Here we report uranium–thorium dating of speleothem formations sampled at Sudwala Cave in the north-eastern Lowveld region of South Africa's summer rainfall zone (SRZ). The growth intervals of multiple formations, alongside a detailed chronology and multi-proxy analysis of two periods of growth, 40–35 ka and 13.8–12.8 ka, in a stalagmite (SC1), provide information regarding key fluctuations in the palaeoclimatic and palaeoenvironmental conditions during the Late Pleistocene. High-resolution stable isotope, trace element, and micro-Raman analysis are used alongside petrographic investigation to provide a detailed assessment of the climatic conditions associated with the onset and termination of growth in SC1. The combined Raman and petrographic analysis represents a rare approach, enabling the identification of aragonite–calcite shifts both within and across growth intervals and diagenetic events, potentially significantly influencing the recorded signal and often resulting in the major loss of chemical information. Consequently, the identification of this post-depositional chemical alteration could become a crucial prerequisite in speleothem palaeoclimatology, particularly in areas prone to aragonite speleothem deposition susceptible to calcite conversion, such as cave sites hosted by dolomitic karst systems. The multiple proxies used in this study highlight the complex forcing relationships between climatically related environmental change and local cave conditions on speleothem precipitation, contesting a common paradigm by associating drier conditions at Sudwala with the initiation of speleothem growth. The growth interval identified in stalagmite SC1 during the late deglaciation (13.85–12.79 ka) coincides convincingly with both the Southern Hemispherically-Forced Antarctic Cold Reversal (14.1–12.8 ka), and the Younger Dryas (12.9–11.5 ka) of Northern Hemispheric origin, identifying Southern Africa as a vital location for the investigation of the hemispheric to global expression of the millennial-scale fluctuations of the last deglaciation. Highlights: Multiple speleothem records from Sudwala Cave located in north east South Africa. Multi-proxy archives from stalagmite SC1 anchored by a robust U–Th chronology. Micro-Raman spectroscopy used to assess the impact of post-depositional alteration. Identification of interhemispheric climate connections in Southern Africa. Links to both the Younger Dryas and Antarctic Cold Reversal.